La Junta para Ampliación de Estudios (1907-1938) y Navarra - Berruezo Albéniz, Reyes (Huarte de San Juan. Geografía e Historia, 2007)
This article sets out to present the knowledge available on the impact that pensions of the JAE had in Navarra. It also announces that, on the occasion of the first centenary of its creation, an interdisciplinary line of research has been set up with the aim of learning more about the relationship of the JAE with Navarre, based on new sources and methodological approaches.